2021
DOI: 10.1371/journal.pone.0244396
|View full text |Cite
|
Sign up to set email alerts
|

An artificial neural network approach to detect presence and severity of Parkinson’s disease via gait parameters

Abstract: Introduction Gait deficits are debilitating in people with Parkinson’s disease (PwPD), which inevitably deteriorate over time. Gait analysis is a valuable method to assess disease-specific gait patterns and their relationship with the clinical features and progression of the disease. Objectives Our study aimed to i) develop an automated diagnostic algorithm based on machine-learning techniques (artificial neural networks [ANNs]) to classify the gait deficits of PwPD according to disease progression in the Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 75 publications
0
20
0
3
Order By: Relevance
“…Machine-learning techniques have been assessed to assist in processing this type of data, and have the ability to differentiate controls from PD cases, as well as different progressive stages of the condition. 104 AUC values of 0.76-0.90 using wearable devices have been obtained, 105 with particular correlation at earlier PD stages, further reinforcing the potential of gait assessment as an objective biomarker. Advanced gait-assessment techniques processed in this way are also able to predict in which patients FoG may arise based on gait parameters, allowing therapies to be targeted early.…”
Section: Wearable Devices and Machine Learningmentioning
confidence: 67%
“…Machine-learning techniques have been assessed to assist in processing this type of data, and have the ability to differentiate controls from PD cases, as well as different progressive stages of the condition. 104 AUC values of 0.76-0.90 using wearable devices have been obtained, 105 with particular correlation at earlier PD stages, further reinforcing the potential of gait assessment as an objective biomarker. Advanced gait-assessment techniques processed in this way are also able to predict in which patients FoG may arise based on gait parameters, allowing therapies to be targeted early.…”
Section: Wearable Devices and Machine Learningmentioning
confidence: 67%
“…In particular, the correlation coefficients revealed that HR AP was lower in subjects with lower pelvic obliquity and pelvic rotation. Alterations in trunk rotation and pelvic kinematics have been consistently described as characteristics of pwPD [ 55 , 88 , 89 ]. Based on our results, we can argue that the trunk rotation rigidity reflected by pelvic rotation and pelvic obliquity leads to alterations in AP trunk smoothness during the gait.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no single optimal classification tool; rather, the best algorithm performance is defined by the studied features [ 32 , 33 ]. In this way, RF appears to be the most robust in the case of a significant reduction in data [ 31 ], ANN is considered an adaptable algorithm with the ability to address nonlinear data [ 34 , 35 ], requiring a large number of parameters for a correct generalization [ 31 ], and DT and KNN benefit from dividing the problem of context recognition into smaller subproblems, which are approached one by one intuitively [ 32 , 36 ]. When assessing the gait of pwPD using IMUs, reducing the number of wearable devices to a single lumbar-mounted sensor allows for sufficient identification of gait abnormalities without significant information loss, reducing the wearability burden in nonlaboratory conditions [ 5 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, supervised ML algorithms should be trained on a set represented by a number of subjects that is approximately 20 times the number of features input into the model [ 47 , 49 ]. When this ratio of features to sample size is respected in studies on gait data and supervised ML, the accuracies of the retrieved models are accurate but less than 90%, reflecting the partial clinical relevance of gait parameters on the multifactorial etiology of pathologies leading to gait disorders [ 10 , 34 , 50 ]. Therefore, particularly for small samples, reducing the number of features in the model may save computational expenditure, reduce the required size of the training set to avoid overfitting [ 47 ], and simplify the medical interpretation of the classifier.…”
Section: Introductionmentioning
confidence: 99%